Diseño de una unidad de estimación de parámetros para un sistema de optimización de energía de uso en paneles fotovoltaicos - Gómez-Ramírez, Pable Esteban (Instituto Tecnológico de Costa Rica, 2017)
In this work, a digital parameter estimation unit for an energy optimization system of photovoltaic panels was implemented. These parameters are necessary to search for the maximum power point in a photovoltaic panel. This documents demonstrates the Verilog design and implementation, the post-implementation simulation and the obtained results.
Proyecto de graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2017.
Keywords: Hardware; Lenguaje; Verilog; Puertas; Matrices; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics